Challenges for the government-controlled higher education system in China. (March 2023) - Xia, Chengqi; Li, Xinge; Cao, Shixiong
Abstract: China's goal is to develop some of the top universities in the world, but there is still a big gap in university quality compared with developed countries. The current command and control system used by the national government limits university autonomy and has created many problems, including a lack of scientific innovation, a widening poverty gap in terms of access to higher education, and a mismatch between supply and demand in the labor market. To solve these problems, China's higher education system must change to permit more autonomy and a stronger focus on the job market; to pay university professors a fair wage; to provide more freedom to the administration of universities and research institutes; and to promote participation by professors in the administration of schools. It will also be important to place less emphasis on awards and titles, and focus instead on letting the best research speak for itself. Highlights: Chinese university education is still guided primarily by the government. This command and control system has limited the development of university education. Universities should compete in the market, guided by government control. Students should be encouraged to become more innovative.